Transdermal administration of radiolabelled [[sup.14]C]rotigotine by a patch formulation: a mass balance trial - Cawello, Willi; Wolff, Hans Michael; Meuling, Wim J.A; Horstmann, Rolf; Braun, Marina (Clinical pharmacokinetics, 2007)
Background and objective: The dopamine agonist rotigotine has been formulated in a silicone-based transdermal system for once-daily administration. The objective of the present study was to characterise the mass balance of rotigotine in humans after administration of a single transdermal patch containing radiolabelled [[sup.14]C]rotigotine and to quantify the pharmacokinetic profiles of total radioactivity and the corresponding rotigotine plasma concentrations. Methods: In a phase I trial, six healthy male Caucasian subjects were administered a single 10 [cm.sup.2] patch containing 4.485mg of unlabelled and 0.015mg of [[sup.14]C]-labelled rotigotine (total radioactivity 0.09 MBq per patch) with a patch-on period of 24 hours. Radioactivity was determined by liquid scintillation counting in unused patches, used patches, skin wash samples after 24 hours, plasma, urine and faeces samples up to 96 hours and skin stripping samples at 96 hours post-application. Unconjugated rotigotine in plasma samples was determined by liquid chromatography with tandem mass spectrometry. Plasma samples were taken predose and 2, 4, 6, 8, 12, 24, 48, 72 and 96 hours after patch application. Results: The rotigotine transdermal patch was well tolerated, and all subjects completed the trial. A total of 94.6% of the administered dose was recovered within 96 hours after patch application inclusive of the residual amounts in the patch. Within 24 hours, 51 % of the total radioactivity was delivered to the human body system and 46.1 % was systemically absorbed. Total radioactivity recovered in urine and faeces was 30.4% and 10.2%, respectively, of the radioactivity applied (corresponding to 65.8% and 21.8% of the dose absorbed, respectively). Conclusions: The mass balance of rotigotine within 96 hours after transdermal delivery of rotigotine via a 10 [cm.sup.2] [[sup.14]C]rotigotine patch with a total drug content of 4.5mg (corresponding to the nominal dose of 2mg/24 hours for the marketed rotigotine transdermal system) has been 95% explained. The systemic absorption was 46.1% of the administered dose, the majority of which was cleared from the body via urine and faeces within 96 hours after patch application.